Advancement of aliphatic polycarbonates with nanoclay addition: An overview / Nur Azrini Ramlee and Nazirul Faiz Mat Noh - Ramlee, Nur Azrini; Mat Noh, Nazirul Faiz (Universiti Teknologi MARA Shah Alam, 2020)
Aliphatic polycarbonates are considered as newly developed biodegradable polymer, which results from a sustainable copolymerization of epoxides and carbon dioxide (CO2) process. These aliphatic carbonates have weak properties in terms of thermal stability and mechanical properties, due to its carbon structure flexibility, hence causing limitation to its applications. Up to date, studies on aliphatic polycarbonates are progressively conducted to maximize its opportunity as an alternative nanocomposite. This review was carried out to provide insights on the progression in producing aliphatic polycarbonates by incorporating various type of fillers to enhance physicochemical, thermal and mechanical properties of aliphatic polycarbonates. The results revealed that a blend of aliphatic polycarbonates/clay nanocomposites with low clay content up to 10 wt.% displayed improved glass transition temperature and thermal degradation in comparison with the pure one. The improved thermal stability was due to the nanoparticle's dispersion into matrix of aliphatic polycarbonates. The mechanical properties such as Young's Modulus and tensile strength of aliphatic polycarbonates were also improved with addition of nanoclay. The improvement of thermal and mechanical properties of aliphatic polycarbonates at low content of nanoclay proves that the addition of nanoclay into polymer matrix is a promising technique to design the properties of aliphatic polycarbonates particularly for the coating application as water and oxygen barrier film.